2020
DOI: 10.1039/d0ra01031f
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)–poly(propylene glycol)–poly(ethylene glycol) and polyvinylidene fluoride blend doped with oxydianiline-based thiourea derivatives as a novel and modest gel electrolyte system for dye-sensitized solar cell applications

Abstract: A unique gel polymer electrolyte was prepared using PVDF and PEG–PPG–PEG block copolymer with I−/I3− for DSSC application. This is a cost-effective method used for the synthesis of thiourea additives. The GPE with OPPT thiourea additive achieved a good efficiency of 5.7%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The conductivity results show that the gel electrolytes with organic additives show better ionic conductivity compared to bare gel polymer electrolytes. 46 The interfacial studies of HEC polymer gel electrolytes with or without organic additives were conducted by fitting the EIS spectrum attained under dark conditions using Z fit software. The experimental data were fitted in terms of equivalent circuits, 59 which are depicted in Figure 2a (inset).…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity results show that the gel electrolytes with organic additives show better ionic conductivity compared to bare gel polymer electrolytes. 46 The interfacial studies of HEC polymer gel electrolytes with or without organic additives were conducted by fitting the EIS spectrum attained under dark conditions using Z fit software. The experimental data were fitted in terms of equivalent circuits, 59 which are depicted in Figure 2a (inset).…”
Section: Resultsmentioning
confidence: 99%
“…The ionic conductivity was calculated using the formula σ = t /( R b A ). Here, t is the thickness of the electrolyte, R b is the bulk resistance, and A is the surface area . The ionic conductivity values of the biogel electrolytes with the BB dye showed an increasing order: 4.46 ×10 –5 S/cm –1 (GE 1) < 5.09 × 10 –5 S/cm –1 (GE 2) < 5.27 × 10 –5 S/cm –1 (GE 3) < 5.42 × 10 –5 S/cm –1 (GE 4) < 5.75 × 10 –5 S/cm –1 (GE 5) < 5.97 × 10 –5 S/cm –1 (GE 6).…”
Section: Resultsmentioning
confidence: 99%
“…Here, t is the thickness of the electrolyte, R b is the bulk resistance, and A is the surface area. 64 The ionic conductivity values of the biogel electrolytes with the BB dye showed an increasing order: 4.46 ×10 −5 S/cm −1 (GE 1) < 5.09 × 10 −5 S/cm −1 (GE 2) < 5.27 × 10 −5 S/cm −1 (GE 3) < 5.42 × 10 −5 S/cm −1 (GE 4) < 5.75 × 10 −5 S/cm −1 (GE 5) < 5.97 × 10 −5 S/cm −1 (GE 6). The above results clearly revealed that the ionic conductivity of a device varies depending on the presence of polymer matrixes and redox couples in the biogel electrolyte.…”
Section: Electrochemical Studiesmentioning
confidence: 99%
“…8 There are a variety of traditional polymer based materials on or aer synthetic polymers and their blends to biopolymer. 8 Some of the well known polymers are polyacrylonitrile (PAN), [9][10][11][12] polyethylene oxide (PEO), 13 polyethylene glycol (PEG), 14,15 poly(methyl methacrylate) (PMMA), 16,17 poly(ethylene glycol) methyl ether methacrylate (PEGMA), 18 poly(vinyl chloride) (PVC), 19 poly(vinylidene uoride) (PVdF) 20 and poly(vinylidene uoride-co-hexauoropropylene) (PVdF-HFP). 21,22 Until now, polysaccharides and modied polysaccharides based materials were in reality for their superior ionic conductivity at room temperature, which includes, for example, chitosan, 23,24 cellulose 25 and carrageenan.…”
Section: Introductionmentioning
confidence: 99%